Breaking the Appalachian barrier : Maryland as the gateway to Ohio and the West, 1750--1850 - Hrastar, John (McFarland and Company, Inc., 2018)
"In 1750 the Appalachian Mountains were a formidable barrier between the British colonies in the east and French territory in the west, passable only on foot or horseback. It took more than a century to break the mountain barrier and open the west to settlement. The Baltimore and Ohio Railroad--the first general purpose railroad in the world--started in Baltimore in the 1820s and reached Wheeling by 1852, uniting east and west"--